Measuring Achievement Motivation as a Useful Tool to Identify Individual Sources of Coping with a Study Load - Ivana Nekvapilova; Jolana Fedorkova; Zdeněk Mikulka; Eva Jirouskova (Communications of International Proceedings, 2020)
Research on coping with a study load at civilian universities has confirmed that students choose both positive and negative coping strategies. However, an important factor that leads to achieving success in coping with the study load is the performance of an individual and his ability to remain in it – his achievement motivation. A standardized questionnaire tool has been developed to measure achievement motivation – the Achievement Motivation Inventory (AMI / the original German abbreviation is LMI), which has so far been used in the field of human resources rather than for the purposes of determining the prerequisites for coping with a study load. The article presents the results of the research into the structure and sources of motivation to perform professionally in the first-year students of the military type of study at military university in the economic and management focus obtained through this questionnaire. The results of each questionnaire were first processed manually in accordance with the standard evaluation procedure and then in Excel. Using a sample of 128 students, it has been proven that in probands, contrary to expectations, the sources of motivation, which are more related to the social conditions of the profession such as status orientation or dominance outweigh those, which are associated with the necessary personality traits to cope with the study load, such as perseverance, commitment, willingness to learn, independence, self-control and purposefulness. The results obtained are used by a military educational institution to tackle the problem of reducing prematurely terminated studies. At the same time, they are the first probe into the determination of motivation to perform in members of generation Z in tertiary education in the Czech Republic. The questionnaire can be recommended as one of the tools that suitably complements the set of diagnostic techniques for examining the student's ability to cope with the demands of the study and allows preventive measures against early school leaving to focus on more precisely. The findings are part of the solution of a specific research project entitled Experience of Foreign Military Universities wit Early Termination of Studies (SV19-FVL-K104-FED).
Keywords: motivation; development; study; achievement / performance; load.